2021
DOI: 10.1002/aenm.202101054
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Multivalent Cation Charge Carriers and Organic Solvents on Nanoporous Carbons in 4 V‐Window Magnesium Ion Supercapacitors

Abstract: Multivalent charge carriers with a smaller ionic radius exhibit strong ionic interactions with solvent molecules. This can lead to unusual characteristics that typically are not observed in conventional monovalent charge carriers. Herein, the capacitive Mg ion storage behavior on nanoporous carbons is investigated within different solvent systems. A larger multivalent charge carrier, Ca ions, and alkali cations with different ionic radii are used as a comparison. In addition, the effects of nanopores on solvat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Table 1 compares the performance of the E-MoS 2 -based MIS with previously reported supercapacitors, including MISs and ZISs based on metal sulfide electrodes, 18,19,21,[62][63][64][65] highlighting its excellent cycling stability for energy storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 compares the performance of the E-MoS 2 -based MIS with previously reported supercapacitors, including MISs and ZISs based on metal sulfide electrodes, 18,19,21,[62][63][64][65] highlighting its excellent cycling stability for energy storage.…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16][17] Most studies on supercapacitors have focused on improving the specific capacity and cycling stability by making full use of the EDLs and pseudocapacitance storage mechanisms. 18,19 EDL charge storage is a very rapid and reversible process, providing high power capability and a stable, long cycle life. However, the relatively small capacity seriously limits the practical application of EDL supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…Moon et al investigated the Mg 2+ ion storage properties of nanoporous carbon with 0.5 M Mg(TFSI) 2 in different organic solvents such as DME, ceric ammonium nitrate (CAN), DMC, and PC. 106 The result showed that the solvent type has little influence on the specific capacitance, while significantly affecting the rate capability. Anyway, the systematic studies are still needed to exploit suitable electrolyte candidate for MgICs as well as other Mg 2+ ion-based energy storage systems.…”
Section: Electrolytes For Nlmicsmentioning
confidence: 98%
“…3i and Table S2) [16,18,28,[31][32][33][34][35][36][37][38]. We also compared other types of supercapacitors in Table S3, showing that ZHSs possess both high security and competitive electrochemical performance [39][40][41][42][43]. These inspiring results reveal that the CPTHB-B2 electrode exhibits rapid dynamics during the electrochemical process, more active sites for charge storage and high reversibility, which can be ascribed to its ultrathin ribbon structure, high heteroatom doping level, rich defects, relatively large surface area and wide pore size distribution.…”
Section: Resultsmentioning
confidence: 84%